Wood potential, biomass and carbon capture in areas left by Erythroxylum coca Lam. (coca) cultivation in Irazola – Ucayali, Peru - Castillo Quiliano, Andrés (2022)
Secondary forests are ecosystems generated by natural or anthropic actions. In the Amazon it occurs basically due to the practice of the slash-and-burn system, for agricultural uses and illegal crops; however, the knowledge of the characteristics, their potentialities and the importance of these are limited. Therefore, the objective of this research was to determine the timber potential, the aerial biomass and the carbon capture of the tree component, in areas that were abandoned after the cultivation of Erythroxylum coca Lam. (coca), at the Macuya Research and Training Center of the National University of Ucayali. Vegetation was evaluated in four plots of 50 × 50 m and 25 sub-plots of 10 × 10 m. In each plot, all tree species, palms, and lianas were recorded and identified, the diameter at breast height from 10 cm, the total and commercial height, were also measured. In this study, 33 families, 72 genera, 85 species in 737 individuals were recorded, the timber potential for current and potential commercial use is comprised of 23 species, with a basal area of 4.89 m2/ ha and a volume of 44.62 m3/ha. Highlighting Cedrela odorata L., Ceiba pentandra (L.) Gaertn. and Minquartia guianensis Aubl. As well as potential species Apeiba aspera Aubl. with 73 trees/ha (47%), basal area 1.30 m2/ha, and volume 8.05 m3/ha and Hieronyma alchorneoides Allemão with 15 trees/ha (10%), 0.23 m2/ha and 1.48 m3/ha. The total aerial tree biomass was 152.03 tB/ha and the carbon stored was 71 tC/ha.